Plants and Mediterranean Flora in Hypnerotomachia Poliphili .......... 143 - Rhizopoulou, Sophia (Tra l’antica sapientia e l’imaginatio: Nuovi studi sul Polifilo, 2020)
This study focuses on botanical aspects gleaned from the literary source Hypnerotomachia Poliphili (1499). Although, imaginary landscapes have been described in Hypnerotomachia Poliphili, vegetative aspects quoted in the text can be linked to literal evidence of plant diversity. Plants such as: roses, myrtle, pines, cypresses, laurel, acanthus, oaks, junipers, ivy, thyme, violets, sandalwoods and orange trees are the most frequently cited. In addition, plants such as: dittany, cypress, fig tree, labdanum, laurel, myrtle, oaks, oleander, wild and cultivated olive trees, oregano, pine, thyme, grapevines are associated with the biodiversity of Mediterranean ecosystems; furthermore, numerous textual passages including flowering and fruiting plants reveal the seasonality of the Mediterranean region. Thorny plants, sharp thistles and cedars are cited in the text as occurring among ancient monuments and historical ruins. Some exotic plants, such as: frankincense tree, myrrh, banana, pepper, sandalwood and jasmines are also included in the treatise. Numerous wild and cultivated plants quoted in the text have been presented as vehicles for expressing emotions, allegory, historical knowledge, environmental attributes and cultural botany, as the world opened up to Renaissance minds.